2010
DOI: 10.1016/j.jcmg.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Thoracic Aortic Atheroma Burden and Long-Term Mortality After Cardiothoracic Surgery

Abstract: Extent of thoracic aortic atheroma burden is independently associated with increased long-term mortality in patients following cardiothoracic surgery. Although our data do not provide definitive evidence, they suggest a relationship to the systemic atherosclerotic disease process and, therefore, have important implications for secondary prevention in post-operative rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…Still, postmortem radiology may provide a feasible alternative in those cases in which no consent for autopsy is given. In such cases, post-mortem can also be used to assessing the extent of aortic atheroma [16].…”
Section: Discussionmentioning
confidence: 99%
“…Still, postmortem radiology may provide a feasible alternative in those cases in which no consent for autopsy is given. In such cases, post-mortem can also be used to assessing the extent of aortic atheroma [16].…”
Section: Discussionmentioning
confidence: 99%
“…First, it did not demonstrate a direct association between plaque growth in the region of low WSS in the basilar artery and brainstem infarction, although atherosclerotic plaque burden is known to be associated with increased long-term mortality 22) . Plaque progression can also lead to increased flow disturbance, resulting in plaque rupture or erosion 23,24) .…”
Section: Conflicts Of Interestmentioning
confidence: 89%
“…Considerable aortic atherosclerotic plaques, which are associated with elevated long-term mortality after cardiothoracic surgery (8), can also be detected with CT. Such findings often lead to a change in surgical strategy- Moodley et al demonstrated that in the case of many patients (87%) who were found to have extensive aortoiliac atherosclerosis or mitral annular calcification (which can also be detected with CT), the strategy was changed from minimally invasive robotic mitral valve surgery to a sternotomy, or the surgery was canceled (9).…”
Section: Imaging In Valve Proceduresmentioning
confidence: 99%